Study on invasion risk of Hydrocotyle vulgaris as an alien species in wetlands - MIAO Li-hua; JI Meng-cheng; WANG Ying-ying; QIAO Dong-dong; CHEN Yu-chu (浙江大学学报. 农业与生命科学版)
The growth habit, morphological and reproductive characteristics of Hydrocotyle vulgaris were systematically described to assess its invasion risks. The results showed that the invasion risks of H. vulgaris were displayed in four aspects. First, the adaptability and phenotypic plasticity of H. vulgaris ensured its adaptation to the environment. Also its tolerance contributed to the occupation of wider ecological amplitude. Second, the aggressive ability made it able to occupy the habitat in high density both ground and underground, which may affect other species and led to a drop in community species diversity. Third, it was apprehended that it had an extremely high reproductive speed, which may grow 50 times each year, due to its vegetative propagation and seed propagation. At last, the difficulties in eradicating and the residue of its tissues also contributed to its rapid reproduction. The climatic standards to identify the potential distribution areas were defined as follows: the number of days whose daily average temperature was stably higher than (or equals) 10℃ were larger than 180 d; the lowest average monthly temperature (January) was higher than -5 ℃; the annually extremely lowest climate temperature was not lower than -10 ℃. According to the meteorological data and climatic characteristics, north subtropical humid region, mid subtropical humid region, south subtropical humid region, edge tropical humid region, mid tropical humid region, equatorial tropical region and plateau subtropical region were identified as the potential distribution areas of H. vulgaris in China. The invasion risk index assessment system indicated that H. vulgaris had a very high risk of invasion with the score of 71, which meant that H. vulgaris was extremely dangerous and was a forbidden species to be introduced. Some suggestions on invasion risk management were proposed on the basis of the growth habit of H. vulgaris.